Oracle PeopleSoft Enterprise Financial Management 9.1 implementation : an exhaustive resource for PeopleSoft financials application practitioners to understand core concepts, configurations, and business processes /: an exhaustive resource for PeopleSoft financials application practitioners to understand core concepts, configurations, and business processes. (2011) - Unknown
No abstract available